(untitled) (Journal of EAHIL, 2020)
Climate change and the COVID-19 pandemic challenge us to re-evaluate the way we live and work. In the academic sector, this includes organising and attending conferences and other scientific meetings. The pandemic has led EAHIL 2020 to be moved online, which is “greener” than physical meetings, but has interactional drawbacks. On the other hand, planning of physical conferences can make use of existing guidance to improve the environmental impact in areas such as venue and travel arrangements, catering, waste reduction as well as communication. In the future, conference organisers can draw upon insights into remote and virtual collaboration gained during the pandemic. Hybrid conferences that allow physical and remote attendance might become an option for increased sustainability of scientific meetings.